THE ROLE OF SCAFFOLDING IN IMPROVING PRESERVICE ELEMENTARY SCIENCE TEACHERS’ SKILLS ON IMPLEMENTING INQUIRY-BASED LEARNING - Hikmawati, Vitta Yaumul (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Inquiry-based learning is considered as an effective learning pathway for teaching science, but unfortunately, elementary preservice science teachers still have an inadequate understanding of inquiry-based learning. This study investigated the role of scaffolding as a supporting method for improving preservice elementary science teachers’ understanding of inquiry-based learning and their skills in implementing inquiry-based learning through peer teaching. Results suggested that scaffolding improves preservice elementary science teachers’ understanding of and skills in implementing inquiry-based learning because features in scaffolding facilitate understanding and teaching skills improvement.